2020
DOI: 10.1186/s13287-020-01729-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD133 in human embryonic stem cell proliferation and teratoma formation

Abstract: Background: Pluripotent stem cells (PSCs), including human embryonic stem cells (hESCs), hold great potential for regenerative medicine and cell therapy. One of the major hurdles hindering the clinical development of PSC-based therapy is the potential risk of tumorigenesis. CD133 (Prominin 1, PROM1) is a transmembrane protein whose mRNA and glycosylated forms are highly expressed in many human cancer cell types. CD133 also serves as a cancer stem cell (CSC) marker associated with cancer progression and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 56 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…Several studies have reported that NRG1 is a predisposition to papillary thyroid cancer, but no genetic variant of NRG1 has been reported about the association with the thyroid cancer risk [ 13 , 25 ]. PROM1 , also known as CD133, is a pentaspan transmembrane glycoprotein that promotes tumor initiation by thyroid cancer stem cells and suppresses cancer cells’ differentiation and helps maintain stem cell properties [ 26 ]. LRP1B is an endocytic receptor that acts as a tumor suppressor by constraining the invasive behaviors of thyroid cancer and other cancer cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that NRG1 is a predisposition to papillary thyroid cancer, but no genetic variant of NRG1 has been reported about the association with the thyroid cancer risk [ 13 , 25 ]. PROM1 , also known as CD133, is a pentaspan transmembrane glycoprotein that promotes tumor initiation by thyroid cancer stem cells and suppresses cancer cells’ differentiation and helps maintain stem cell properties [ 26 ]. LRP1B is an endocytic receptor that acts as a tumor suppressor by constraining the invasive behaviors of thyroid cancer and other cancer cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various human cancer cell types express mRNA and glycosylated forms of CD113. It also acts as a CSC (cancer stem cell) marker and hence plays pivotal role in induction of inflammation, tumor initiation, progression, invasion, and metastasis [139–141].…”
Section: Benzimidazole As Target Oriented Anticancer Agentsmentioning
confidence: 99%
“…Still, the proliferating potential is reduced and results in reduced teratoma formation[ 51 ]. Therefore, CD133 may be used to sort ESCs for transplantation[ 52 ].…”
Section: Current Trends In the Therapeutic Use Of Stem Cellsmentioning
confidence: 99%